Enhanced Organic Pollutant Adsorption Using Zeolite-Carbon Dots Composites Synthesized by the Impregnation Method - Thanh, Ho Tan; Phuc, Nguyen Thien; Khoi, Dang Dinh; Long, Nguyen Quang (Indonesian Journal of Chemistry, 2026)
In this study, a novel zeolite–carbon dots (ZCD) composite was synthesized via impregnation to enhance the adsorption performance of zeolite. The attachment of carbon dots (CDs) onto the zeolite surface was confirmed by SEM/EDS, TEM, BET, and FT-IR analyses. These results showed that CDs were uniformly dispersed on the FAU-type zeolite, introduced additional –OH, –CHx, and –NH2 groups, and increased the BET surface area from 444.5 to 491.5 m2 g−1. The presence of functional groups on the surface of CDs enhanced the adsorption capacity of zeolite. Notably, ZCD exhibited a 45% higher adsorption capacity for methylene blue (MB) than pristine zeolite, with a maximum experimental uptake of 32.53 mg g−1. Adsorption isotherm and kinetic studies, best described by the Langmuir model (qm = 29.22 mg g−1, R2 = 0.9815) and the pseudo-second-order kinetic model (R2 = 0.9991), indicated that MB uptake on ZCD occurred through both physical and chemical interactions. These results suggest that the ZCD composite is a promising adsorbent for the removal of organic dyes in water treatment applications.